Investigation into the characteristics of H2-rich gas injection over iron ore sintering process: Experiment and modelling. (5th July 2019) - Huang, Xiaoxian; Fan, Xiaohui; Ji, Zhiyun; Gan, Min; Chen, Xuling; Zhao, Yuanjie; Jiang, Tao
Highlights: H2 -rich gas injection (HGI) improved sinter quality and abated pollutants emissions. HGI decreased solid fuel and moisture consumption for sintering. Deep mechanism of HGI on sintering was revealed via experiments and modelling. Abstract: Applying hydrogen energy into iron ore sintering process is an efficient strategy to abate CO2 emission. This investigation mainly focused on revealing the influence of H2 -rich gas injection on sintering performance and elucidating the deep mechanism through both laboratory tests and mathematical model. Results showed that injecting H2 -rich gas contributed to reducing the proper moisture content and coke breeze rate from 7.00% and 5.60% to 6.75% and 5.30% due to the negative influence of generated H2 O and excessive heat supply. Under main operation conditions, increasing the injection concentration of H2 -rich gas improved the sinter yield and tumbler index gradually till reaching the proper concentration of 0.80%. The emission reduction of NO and SO2 mainly brought by the decreased coke breeze consumption reached around 10% and 6%. The mechanism of H2 -rich gas injection was mainly attributed to the improved thermal patterns of sintering bed, which increased liquid phase formation area and high temperature (≥1200 °C) duration, thereby facilitating the formation of enough adhesive phase calcium ferrite. Moreover, the cooling velocity of adhesive minerals was obviously slowed down, which facilitated the formation of needle-like calcium ferrite with high mechanical strength. The research findings are of great significance for guiding the application of cost-effective H2 -rich gas into practical sintering plants.